2013
DOI: 10.7883/yoken.66.411
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Measles- and Mumps-Specific Immunoglobulin G among Japanese Healthcare Students Increased during 2007–2012

Abstract: SUMMARY:We evaluated the seroprevalence of vaccine-preventable infectious diseases among Japanese healthcare students to create immunization guidelines. Between 2007 and 2012, a total of 1746 Japanese medical, nursing, and paramedical students were serologically screened for measles, mumps, rubella, varicella, and hepatitis B virus (HBV) antibodies at the time of admission. In 2007, the seroprevalence of measles and mumps was 52.7z and 65.6z, respectively. The seroprevalence of measles dramatically increased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…2008 to 2012 (Kimura et al 2013;IDSC, NIID 2015). In 2013, a nationwide rubella epidemic occurred in Japan, and an increase in CRS was reported (CDC 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2008 to 2012 (Kimura et al 2013;IDSC, NIID 2015). In 2013, a nationwide rubella epidemic occurred in Japan, and an increase in CRS was reported (CDC 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to eliminate measles and rubella, the Japanese government implemented a two-dose measlesrubella vaccination schedule during childhood in 2006 (IDSC, Infectious Disease Surveillance Center, NIID, National Institute of Infectious Diseases 2007) and a 5-year measles-rubella catch-up vaccination campaign conducted from 2008 to 2012 for cohorts aged 13 and 18 years (Kimura et al 2013;IDSC, NIID 2015). In Japan, the person who was born after 2006 receives two-dose measlesrubella vaccination aged 1 year and 5 years, on the other hand, the person who was born between 1995-2005 received two-dose measles-rubella vaccination aged 1 year and 13 years.…”
Section: Introductionmentioning
confidence: 99%
“…There were five measles [6,12,13,19,20] and 10 rubella studies [6,12,14,19,25,43,44,63,74,87] in category 2. Each study reported testing specimens obtained from individuals having a range of ages, from infants to adulthood, and compared the seroprevalence in each age group.…”
mentioning
confidence: 99%
“…Additionally, seroprevalence rates among adolescents and young adults were similar to those reported previously in these age groups in the Japanese population. 10,16 Finally, because the evaluation rates of seroprevalence change between two study periods were conducted using serial 5-year birth cohorts, except infants aged <1 year old, we were only able to specify the 5-year age range in children most affected by the mumps epidemic.…”
Section: Discussionmentioning
confidence: 99%